EFISIENSI KERJA CHRUSING PLANT PT. NUR HAZANAH KARYA ABADI DISTRIK PRAFI KABUPATEN MANOKWARI PROVINSI PAPUA BARAT - Albertina Awom; Yulius G. Pangkung (INTAN Jurnal Penelitian Tambang, 2021)
This study aims to determine the efficiency of the crushing plant at PT. Nur Hazanah Karya Abadi, using a descriptive method, describes the state of the object of research directly. It is known that the average efficiency value based on the availability of mechanical equipment is effectiveness 67.8%, availability of mechanical/physical 67.15%, utility 36.5%, and optimum efficiency 34.85%. Based on the work assessment table, the crushing plant efficiency is classified as very bad, due to the optimum efficiency value below 58%.